PENGARUH BIAYA OPERASIONAL TERHADAP LABA BERSIH PERUSAHAAN BUMN DISEKTOR MANUFAKTUR YANG TERDAFTAR DIBURSA EFEK INDONESIA PADA PERIODE 2017-2024 - indra firmansyah indra; Tessalonika simanjuntak (LAND JOURNAL, 2026)
Net profit is a crucial element in a company. To achieve the desired net profit, companies must develop sound planning. In a financial structure, operating costs are two important components that can affect net profit. This study examines The impact of operating expenses on net profits in state-owned manufacturing, companies listed on the (IDX). This research uses a quantitative approach, utilizing secondary data in the form of company financial reports. Various statistical methods are applied, such as normality tests, product-moment tests, simple linear regression tests, coefficient of determination tests, and t-tests. Based on the t-test results, operating costs are proven Shows a significant partial impact on net income.